SUMBERDAYA BATUAN DAN PEMANFAATANNYA PADA BEBERAPA SITUS MEGALITIK DI KAWASAN JEMBER - Fadhlan S. Intan (Berkala Arkeologi, 2001)
The Jember area is very suitable to serve as a megalithic settlement location. This area is supported by geological conditions which are generally very supportive. Abundant natural resources (rocks, water) have been optimally utilized by megalithic communities in the Jember area. The megalithic community of Jember has applied the concept of adaptation in maintaining their lives.